2011
DOI: 10.1074/mcp.m111.007930
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response to Membrane Protein Overexpression in E. coli

Abstract: Overexpression represents a principal bottleneck in structural and functional studies of integral membrane proteins (IMPs). Although E. coli remains the leading organism for convenient and economical protein overexpression, many IMPs exhibit toxicity on induction in this host and give low yields of properly folded protein. Different mechanisms related to membrane biogenesis and IMP folding have been proposed to contribute to these problems, but there is limited understanding of the physical and physiological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 49 publications
8
57
0
1
Order By: Relevance
“…The nonsense allele that we observed in newer MG1655 stocks was also recently noted in strains obtained from the E. coli genome project by Gubellini and coworkers (8) and presumably arose because the sequenced strain was, at various points during the sequencing process, grown on glycerol as a carbon source (F. Blattner, personal communication). Different defective glpR alleles have also been observed previously in other K-12 lineages (12,14) and may likewise reflect the common use of glycerol as a carbon source in laboratory cultures.…”
supporting
confidence: 71%
“…The nonsense allele that we observed in newer MG1655 stocks was also recently noted in strains obtained from the E. coli genome project by Gubellini and coworkers (8) and presumably arose because the sequenced strain was, at various points during the sequencing process, grown on glycerol as a carbon source (F. Blattner, personal communication). Different defective glpR alleles have also been observed previously in other K-12 lineages (12,14) and may likewise reflect the common use of glycerol as a carbon source in laboratory cultures.…”
supporting
confidence: 71%
“…This absence of stress response induction is consistent with what has been observed for a variety of integral membrane proteins in a very recently published study (Gubellini et al, 2011). Overexpression of NTR1(D03) together with nlpDΔ(349-380), however, resulted in a significant increase in transcription from P3rpoH, PftsH, and PppiD, promoters (3.5-, 2.9-, and 2.7-fold, respectively) compared to the empty plasmid control and, to a lesser extent, from the PppiA, PbolA and Plon promoters (2.3-, 2.3-, and 2.1-fold, respectively) (Figure 4).…”
Section: Nagd and Nlpdδ (349-380) But Not Ptsn-yhbj-npr Induce Selesupporting
confidence: 92%
“…Initially, we attempted the TA cloning method and also the directional cloning method using inducible expression vectors such as pET and pBAD to clone G3Pp4, but without success. We concluded that our initial efforts to clone the G3Pp genes might have been hindered by the toxicity of these proteins in E. coli cells, because some members of the MFS are reportedly difficult to be cloned or expressed in homologous and heterologous systems due to their toxicity (Elashvili et al 1998;Frohlich et al 2010;Gubellini et al 2011). In the present study, fortunately, G3Pp4 was successfully cloned into an entry vector for the Gateway TM Cloning System.…”
Section: Discussionmentioning
confidence: 72%